Disease activity and changes in the fibrosis-4 index in patients with rheumatoid arthritis treated with methotrexate for a short period - Noriyuki Namura; Kazuya Kamada; Takahumi Hagiwara; Kanae Takahashi; Kiyoshi Matsui (Archives of Rheumatology, 2025)
Objectives: This study aims to investigate the relationship between disease activity and changes in the fibrosis-4 index (FIB-4) in patients with rheumatoid arthritis (RA) who received methotrexate as Phase I treatment for a short period. Patients and methods: In this retrospective study, 144 patients (106 females, 38 males; median age: 68.05 years; range, 58.3 to 76.0 years) diagnosed with RA who had not received methotrexate before their diagnosis were included between April 2015 and September 2020. The patients’ clinical data were recorded at baseline, six months, and 12 months. Patients with hepatitis, alcoholism, severe obesity, hypercholesterolemia, or overlapping autoimmune diseases and those receiving a maximum methotrexate dose of ≤10 mg/week were excluded. Multiple regression analysis was performed to identify predictors of the changes in FIB-4 values from baseline. Mediation analysis was employed to determine the association between Disease Activity Score-28 for RA with erythrocyte sedimentation rate (DAS28-ESR) and changes in FIB-4 values, with the cumulative methotrexate dose as a mediator. Results: FIB-4 values increased significantly from baseline to 12 months after methotrexate initiation. The cumulative methotrexate dose did not independently influence changes in FIB-4 values. After adjusting for confounding factors, the factor independently influencing the change in fibrosis-4 values from baseline was DAS28-ESR at six and 12 months (β=0.107 and β=0.086, respectively). The cumulative methotrexate dose did not mediate the relationship between DAS28-ESR at baseline and changes in FIB-4 values, and it did not affect changes in FIB-4 values over a short period. Conclusion: Rheumatoid arthritis disease activity before methotrexate administration independently affected changes in FIB-4 values. We suggest monitoring FIB-4 values in patients with RA with high disease activity, even for a short period after methotrexate administration, as FIB-4 values in these patients may be underestimated.